The competitiveness of South African chemical firms and their expansion into the rest of Africa - Ntuli, Mphathisi (My University, 2016)
The purpose of this research is to explore the current challenges of competitiveness faced by South African chemical firms in selected sub-sectors of the chemical industry, with respect to both their domestic competitiveness and their ability to expand into the rest of Africa from a dynamic capabilities perspective. Whilst the general innovation literature has treated dynamic capabilities from a general firm level, it seems that there is very little work that has been done in the chemical industry, particularly in the South African context. Therefore, this is an area of academic research that offers bountiful opportunities to build on, and insightful findings from different industries and different geographical contexts are useful for the critical engagement of the theoretical framework. Preliminary research shows that South African chemical companies are not competing effectively, primarily due to the legacy of protectionism and isolationism during the apartheid period. This fostered an inward looking approach and a focus on import substitution in the local market. As a result, it encouraged the building of small scale plants with capacity geared for local demand. However, it appears that this approach was not particularly profitable during the same period, but it was carried out nonetheless for political reasons aligned with the interests of the erstwhile regime. Post-1994, after the new democratic dispensation in South Africa, this situation was followed by an influx of cheap imports, high raw material prices due to import tariffs and volatile exchange rates, and this brought competitiveness challenges to domestic firms. This was exacerbated by inadequate capacities and capabilities to overcome these challenges. Notwithstanding this, a number of firms seem to have survived, due to a number of reasons, which include management processes, organisational processes, location advantages, as well as with respect to their ability to expand beyond the borders of the country including their choice of entry strategy. iii The research methodology was an exploratory and qualitative study involving three firms. These firms were purposively chosen using a predefined criterion. Firstly, the selected South African chemical firms are assumed to possess business strategies that are unique, differentiated enough to make it difficult for competitors to imitate. Secondly, they are deemed to possess a location advantage if manufacturing locally versus a competitor who is importing. The findings of the study show that these firms possess firm-specific processes, capabilities and positions within the industry that make them competitive for a while but also enable them to adapt to changes in their customer needs. The findings also show that these firms leverage resources in the form of consolidation and collaboration between various business units to achieve cost efficiencies and economies of scale. Although these firms possess a location advantage, the findings show that they are not competitive if the target market is closer to the coast as a majority of them are based inland. On the flip side, the findings show that they do not put much effort into either radical or disruptive innovation, but have an incremental form of innovation. Furthermore, they do not seem be doing well in terms of long term commitment of resources to enhance organisational learning as a response to the changing environment. Also, they have been relaxed and slow in sensing, shaping and seizing opportunities and mitigating threats due to their internal focus. Now that things are changing quickly, their reactions seem to be a bit late. From the research, it can be argued that the decision about which African country to expand to, as well as the choice of an entry strategy to adopt, depends on various factors. These include the country’s risk profile, regulations and language among others. Furthermore, the findings suggest that these South African chemical firms have very similar structured procedures that they follow in choosing which African country to expand to as well as in choosing which entry strategy to adopt. Therefore, based the afore-stated findings, it can be recommended that in order to improve their competitiveness, South African chemical firms need to put more effort into innovation, diversity, learning behaviours, awareness of the internal and external environment, improved channels of communication for information iv flow, and better understanding of the capabilities that they possess and need. However, the limitation of this research is that it focuses on three firms in the South African chemical industry. Therefore, the findings cannot be generalised to cover all of the industry. Future research should consider a large cross-sectional study of the entire industry. In addition, the study only looks at firms which are deemed to be competitive. There could be a need to look at firms which fail to be competitive domestically or abroad, or both, to give a balanced view of the extent to which their failure can be explained by the dynamic capabilities framework.
MBA
Keywords: Chemical industry -- South Africa.